2005
DOI: 10.1002/pon.902
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and behavioural functioning of children of a parent diagnosed with cancer: a cross-informant perspective

Abstract: This study investigates emotional and behavioural problems in children of parents diagnosed with cancer and examines the relationship with demographic and illness-related variables. Furthermore, agreement and differences between informants regarding child's functioning were examined. Members of 186 families in which a parent had been diagnosed with cancer participated. More emotional problems were reported for latency-aged sons (ill parents) and adolescent daughters (ill parents; self-reports), whereas also be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
125
7
14

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(158 citation statements)
references
References 32 publications
12
125
7
14
Order By: Relevance
“…The YSR and TRF are parallel versions of the original CBCL instrument designed to measure the same variables by each type of informant; for brevity's sake they will all be referred to here as 'CBCL measures'. Following previous studies (Visser et al, 2005;Lewis et al, 2005), Internalising, Externalising and Total Problem scores will be examined here as indices of child problems. For ethical reasons, six items about bowel and sexual problems were omitted from the CBCL.…”
Section: Child Emotional and Behavioural Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The YSR and TRF are parallel versions of the original CBCL instrument designed to measure the same variables by each type of informant; for brevity's sake they will all be referred to here as 'CBCL measures'. Following previous studies (Visser et al, 2005;Lewis et al, 2005), Internalising, Externalising and Total Problem scores will be examined here as indices of child problems. For ethical reasons, six items about bowel and sexual problems were omitted from the CBCL.…”
Section: Child Emotional and Behavioural Problemsmentioning
confidence: 99%
“…Previous research suggests that adolescent children experience most problems (Welch et al, 1996;Birenbaum et al, 1999), with teenage daughters being most at risk (Wellisch et al, 1992;Compas et al, 1994). Visser et al (2005)reported that adolescent daughters were more affected by parent's cancer treatment intensity whereas for boys it was relapse of cancer. However, the evidence on gender differences remains insubstantial given the low number of studies including boys.…”
mentioning
confidence: 99%
“…However, to assess children's burden, another perspective might be needed because parents often underestimate their children's distress regarding cancer. 30 The finding that patients reported the highest need for support for their families and children during medical treatment indicates that patients should be screened for distress during this period and should be given brief emotional support on how to talk with children about cancer and its effects on the future. This confirms the need to educate health professionals about the psychological burden of patients' children.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, several qualitative studies suggested that children worry about their ill parents more than parents may know, 2,3 use a range of coping strategies to keep life as normal as possible, 2-4 and appreciate communication about the parent's illness. [4][5][6] Largerscale studies using standardized measures have demonstrated that a parent's cancer can be distressing to children of all ages 7,8 and that its impact is partly moderated by family cohesion, communication, the quality of the parents' relationship with each other, and parents' psychosocial functioning (particularly maternal depression). [9][10][11][12][13] There remains a great need for longitudinal research to identify the range of developmental trajectories experienced by children living with a parent's cancer and whether some children, with adequate support, emerge with new strengths such as enhanced problem-solving skills or richer support networks.…”
mentioning
confidence: 99%